2010
DOI: 10.3184/030823410x12857507693319
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Electrochemical Oxygenation of Thiophenes, Benzo[b]Thiophenes and Dibenzothiophenes; Photochemical and Electrochemical Behaviour of Their Oxygenated Intermediates and Products

Abstract: Prof. Dr. Thies Thiemann received his chemical education at the universities of Hamburg and Tuebingen, Germany. After obtaining a PhD degree in organic chemistry at the University of Hamburg, he moved to Japan for his postdoctorate at Kyushu University, Fukuoka. Thies has also worked at joined the chemistry faculty of the United Arab Emirates University in Al Ain, Abu Dhabi. His main focus is on organic synthetic chemistry, especially in the areas of steroidal and heterocyclic chemistry. He is author/co-author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…30) have shown that illuminated P3HT, like many organic chromophores, is indeed a generator of singlet oxygen. In the same publication however, Manceau et al demonstrated that singlet oxygen is very unreactive with polythiophene, as has been suggested elsewhere, 40 hence singlet oxygen is not thought to go on to react to form an oxygenated defect state with P3HT, as marked out in the scheme. The most likely route for oxygenated defect formation therefore is by direct conversion from the charge transfer intermediate state.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…30) have shown that illuminated P3HT, like many organic chromophores, is indeed a generator of singlet oxygen. In the same publication however, Manceau et al demonstrated that singlet oxygen is very unreactive with polythiophene, as has been suggested elsewhere, 40 hence singlet oxygen is not thought to go on to react to form an oxygenated defect state with P3HT, as marked out in the scheme. The most likely route for oxygenated defect formation therefore is by direct conversion from the charge transfer intermediate state.…”
Section: Discussionmentioning
confidence: 66%
“…Of the polymer degradation studies available, studies have primarily focused on the prevalent polyphenylvinylene (PPV) [24][25][26][27][28][29] and polythiophene (PT) 26,[29][30][31][32][33][34][35][37][38][39][40] family of polymers. A degradation pathway for conjugated polymers that is well supported by studies is oxidation via radical formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The products could be either a mono-or di-oxidized sulfur atom. [61][62][63] The S-O products are more likely to occur on thiophenes that are a part of a larger conjugated system, such as benzodithiophene, than those that are more isolated due to lower energy barriers. 61 Combining these results, Fig.…”
Section: Case Examples For Degradationmentioning
confidence: 99%